Hastes intramedulares flexíveis no tratamento de fraturas da diáfise do úmero em adultos: um estudo fase I - Luft, Michel (2015)
The treatment for the humeral shaft fractures in adults usually presents two possibilities of management: conservative treatment and surgical treatment. The conservative treatment is administered through the use of cast and the surgical treatment can be provided with the use of plates and screws or with the use of rigid intramedullary nails. Flexible intramedullary nails are widely used in the treatment of long bone fractures in children. We aim to use flexible intramedullary nails in the treatment for humeral shaft fractures in adults and assess the consolidation time, pain and the rehabilitation results. The research was conducted through the selection of twenty cases of humeral shaft fractures in adults in which the treatment was provided with the use of flexible intramedullary nails. The results were satisfactory, with good signs of approval regarding the management of the fractures. From the positive results that were obtained, we expect to increase the number of cases treated with flexible intramedullary nails and to compare them with control groups that have undergone other forms of treatment for these fractures.